Morphological abnormalities in mites of the genera Zercon and Prozercon (Acari: Gamasina) collected near caves: preliminary results - Barczyk, Gabriela; Madej, Grażyna (Biological Letters, 2012)
Eleven mites of the genera Zercon C. L. Koch, 1836 and Prozercon Sellnick, 1943 with various morphological deviations (changes in chaetotaxy) are described. The mites were collected from the natural environment, near limestone caves in the Kraków-Częstochowa Upland (Wyżyna Krakowsko-Częstochowska) in southern Poland.